2014
DOI: 10.3109/17435390.2013.879342
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to zinc oxide nanoparticles does not affect the cognitive capacity and neurotransmitters levels in adult rats

Abstract: With the industrialization and increasing public exposure, nano-sized materials have received much more concerns. However, the impact of zinc oxide nanoparticles (ZnO-NPs) on the human body, especially on the central nervous system is extremely limited. The aim of this study is to investigate the effects of ZnO-NPs on the behavioral performances and the brain contents of some monoamines neurotransmitters. Male Wistar rats were treated with a single intravenous injection of a suspension of ZnO-NPs (25 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
6
28
0
Order By: Relevance
“…This finding was further confirmed by the results from another toxicity study 67 in which zinc concentrations in rat brains increased significantly after an intravenous injection of a suspension of ZnO NPs for 14 consecutive days. The study also found that the concentration of neurotransmitters in the brain, such as norepinephrine and epinephrine, remained unchanged.…”
Section: In Vivo Studies On the Potential Toxicity Of Nanomaterials Osupporting
confidence: 77%
“…This finding was further confirmed by the results from another toxicity study 67 in which zinc concentrations in rat brains increased significantly after an intravenous injection of a suspension of ZnO NPs for 14 consecutive days. The study also found that the concentration of neurotransmitters in the brain, such as norepinephrine and epinephrine, remained unchanged.…”
Section: In Vivo Studies On the Potential Toxicity Of Nanomaterials Osupporting
confidence: 77%
“…Male Wistar rats were treated with a single intravenous injection of a suspension of ZnO-NPs in Amara et al's study. 8 The results indicated that plasma and brain zinc concentrations increased after the administration of ZnO-NPs. Han et al 9 used…”
Section: Introductionmentioning
confidence: 74%
“…Briefly, wild-type BV-2 cells, BV-2 cell clones transfected with an empty vector, and PC12 cell clones transfected with PINK1 siRNA were seeded in a 96-well culture plate at a density of 5×10 3 cells/well and incubated overnight for cell attachment. Next, the cells were rinsed with PBS and treated with 10 μg/mL ZnO NPs for 4,8,12, and 24 h. Then, the cells were washed with PBS twice and incubated with 10 μM of DCFH-DA for 1 h. Subsequently, DCF fluorescence intensity was measured using a Synergy-4 microplate reader (Biotek Instruments Inc., Winooski, VT, USA) at an excitation wavelength of 485 nm and an emission wavelength of 535 nm.…”
Section: Rosmentioning
confidence: 99%
See 2 more Smart Citations